On branches of small solutions of certain operator equations - Dymarskii, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
In the case of double degeneration of a linearized problem, we study the points of bifurcation of the null solutions of nonlinear equations of special type.